2022
DOI: 10.1021/acsami.1c21378
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Modified Nano-Bioactive Glass for Targeted Immobilization of Native VEGF

Abstract: A limiting factor in large bone defect regeneration is the slow and disorganized formation of a functional vascular network in the defect area, often resulting in delayed healing or implant failure. To overcome this, strategies that induce angiogenic processes should be combined with potent bone graft substitutes in new bone regeneration approaches. To this end, we describe a unique approach to immobilize the pro-angiogenic growth factor VEGF 165 in its native state on the surface of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…85 Schumacher et al developed a growth factor VEGF immobilization system based on the PR1P polypeptide, which can bind VEGF with high specificity for bone regeneration in vivo. 86 In a different approach, Ito et al developed a coupling peptide to increase the affinity of folate for the folate receptor (FR) by adding 4-acid phenylalanine and diphenylcyclooctene (DBCO) to the peptide. 78 The experimental results demonstrated that conjugation of peptides with biotin is a powerful tool to improve targeting capabilities in drug delivery applications.…”
Section: Applications Of Peptides Combined With Biomacromoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…85 Schumacher et al developed a growth factor VEGF immobilization system based on the PR1P polypeptide, which can bind VEGF with high specificity for bone regeneration in vivo. 86 In a different approach, Ito et al developed a coupling peptide to increase the affinity of folate for the folate receptor (FR) by adding 4-acid phenylalanine and diphenylcyclooctene (DBCO) to the peptide. 78 The experimental results demonstrated that conjugation of peptides with biotin is a powerful tool to improve targeting capabilities in drug delivery applications.…”
Section: Applications Of Peptides Combined With Biomacromoleculesmentioning
confidence: 99%
“…Fan et al designed the BIF polypeptide that binds to vimentin, blocking vimentin skeletonization to inhibit tumor cell migration and invasion . Schumacher et al developed a growth factor VEGF immobilization system based on the PR1P polypeptide, which can bind VEGF with high specificity for bone regeneration in vivo . In a different approach, Ito et al developed a coupling peptide to increase the affinity of folate for the folate receptor (FR) by adding 4-acid phenylalanine and diphenylcyclooctene (DBCO) to the peptide .…”
Section: Applications Of Peptides Combined With Biomacromoleculesmentioning
confidence: 99%
“…When injected subcutaneously into mice, it has also been shown to promote the expression of proangiogenic factors, such as insulin-like growth factor 2 (IGF-2), interleukin 6 (IL-6), VEGF, interleukin 1 beta (IL-1β), interleukin-12 (IL-12p70), granulocyte–macrophage colony-stimulating factor (GM-CSF), and others, therefore, stimulating bone regeneration as well as vascular growth [ 195 ]. Another substance that can stimulate bone regeneration and angiogenesis is nanobioactive glass, which has a three-dimensional (3D) channel framework and a larger surface area [ 240 ].…”
Section: Bone Regenerationmentioning
confidence: 99%
“…PR1P was also used to modify biomaterial scaffold. By chemical covalent coupling, RP1P could immobilize VEGF on nano glasses effectively and increase the bioactivity of material scaffolds 19 . In addition, specific chimeric peptides consisting of PR1P were also used to modify 3D‐Titanium (Ti) implant surfaces by chemical cross‐linking and showed to promote osseointegration by promoting angiogenesis and osteogenesis 20 .…”
Section: Introductionmentioning
confidence: 99%
“…By chemical covalent coupling, RP1P could immobilize VEGF on nano glasses effectively and increase the bioactivity of material scaffolds. 19 In addition, specific chimeric peptides consisting of PR1P were also used to modify 3D-Titanium (Ti) implant surfaces by chemical crosslinking and showed to promote osseointegration by promoting angiogenesis and osteogenesis. 20 Unlike the regeneration of hard tissues such as bone, the methods by chemical covalent coupling usually led to the stiffness of biomaterial and retarded the degradation of biomaterial, which would impact the restoration of cardiac function in the repair of MI.…”
mentioning
confidence: 99%